2012
DOI: 10.1071/py10084
|View full text |Cite
|
Sign up to set email alerts
|

Australian health professionals’ social media (Web 2.0) adoption trends: early 21st century health care delivery and practice promotion

Abstract: This study was concerned with identifying reasons behind patterns of social media (Web 2.0) usage associated with eight of Australia's major health professions. Attention was given to uncovering some of the more significant motivations for the resistance or adoption of Web 2.0 technologies for health care delivery and practice promotion by Australian health professionals. Surveys were developed from a common set of questions with specific variations between professions negotiated with professional health socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…A few studies had previously highlighted the reasons for adopting social media tools by physicians. For example, Usher 7 found that Australian physicians adopt social media because it provides a quick and effective way to communicate; has the ability to be used effectively; is appealing for younger patients; they have had requests from patients; it is enjoyable; it has ease of mobility; and it provides a forum for finding relevant health information. 30 Hughes et al 9 have also revealed that junior physicians are interested in Web 2.0 tools because of their ease of use, their structure, and the breadth of information that these sites provide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies had previously highlighted the reasons for adopting social media tools by physicians. For example, Usher 7 found that Australian physicians adopt social media because it provides a quick and effective way to communicate; has the ability to be used effectively; is appealing for younger patients; they have had requests from patients; it is enjoyable; it has ease of mobility; and it provides a forum for finding relevant health information. 30 Hughes et al 9 have also revealed that junior physicians are interested in Web 2.0 tools because of their ease of use, their structure, and the breadth of information that these sites provide.…”
Section: Discussionmentioning
confidence: 99%
“…4 Despite the evidence demonstrating the increasing use of social media by many medical practitioners and organizations, it is still nascent and underutilized in the healthcare domain and currently there is a widespread skepticism about and mistrust of the usefulness of social media in healthcare. 6 Although some studies [7][8][9] investigated the adoption of social media by healthcare professionals, most predominantly focused on revealing the patterns of use and the level of physicians' familiarity with social media tools. Very few studies have discussed in detail the potential benefits and challenges of adopting social media by physicians.…”
Section: Introductionmentioning
confidence: 99%
“…As many aspects of social media use by healthcare professionals are under-explored, there is a need for further studies to investigate how physicians and other healthcare professionals connect, trust and share knowledge with each other online. In particular, very few studies have explored how physicians trust peers on social media, especially as related to medical knowledge and information important in patient care 4. Therefore, the aim of this study was to identify approaches through which physicians develop and sustain mutual trust on social media.…”
Section: Introductionmentioning
confidence: 99%
“…Australian research involving a survey of health care professionals' attitudes to and use of social media conducted in 2009 (Usher, 2011(Usher, , 2012 found that less than 10% of the respondents used social media for work purposes. The main reason for not adopting social media use for health care delivery was lack of understanding about how to do so.…”
Section: Research-article2017mentioning
confidence: 99%